Assessing the quality of health care in the management of bronchiolitis in Australian children: a population-based sample survey. Issue 10 (2nd April 2019) - Homaira, Nusrat; Wiles, Louise K; Gardner, Claire; Molloy, Charlotte J; Arnolda, Gaston; Ting, Hsuen P; Hibbert, Peter Damian; Braithwaite, Jeffrey; Jaffe, Adam
Abstract : Background: Bronchiolitis is the most common cause of respiratory hospitalisation in children aged <2 years. Clinical practice guidelines (CPGs) suggest only supportive management of bronchiolitis. However, the availability of CPGs do not guarantee that they are used appropriately and marked variation in the clinical management exists. We conducted an assessment of guideline adherence in the management of bronchiolitis in children at a subnationally representative level including inpatient and ambulatory services in Australia. Methods: We searched for national and international CPGs relating to management of bronchiolitis in children and identified 16 recommendations which were formatted into 40 medical record audit indicator questions. A retrospective medical record review assessing compliance with the CPGs was conducted across three types of healthcare setting: hospital inpatient admissions, emergency department (ED) presentations and general practice (GP) consultations in three Australian states for children aged <2 years receiving care in 2012 and 2013. Results: Purpose-trained surveyors conducted 13 979 eligible indicator assessments across 796 visits for bronchiolitis at 119 sites. Guideline adherence for management of bronchiolitis was 77.3% (95% CI 72.6 to 81.5) for children attending EDs, 81.6% (95% CI 78.0 to 84.9) for inpatients and 52.3% (95% CI 44.8 to 59.7) for children attending GP consultations. While adherence to some individual indicators was high, overall adherence to documentation of 10 indicators relating to history taking and examination was poorest and estimated at 2.7% (95% CI 1.5 to 4.4). Conclusions: The study is the first to assess guideline-adherence in both hospital (ED and inpatient) and GP settings. Our study demonstrated that while the quality of care for bronchiolitis was generally adherent to CPG indicators, specific aspects of management were deficient, especially documentation of history taking.